Efecto de la manzanilla en el agua de bebida sobre el rendimiento productivo y salud en pollos de engorde Cobb 500 - Once Santos, Cindy Lissette (2025)
The objective of this research was to analyze the impact of the inclusion of chamomile in the drinking water on the productive and health parameters of the Cobb 500 chickens, for which data were collected during six weeks, which were used to obtain results such as: weight gain in gr, mortality, feed consumption in gr, consumption of water infused with chamomile in ml, benefit-cost ratio. The experimental design used was a completely randomized design (CRD) with 100 Cobb 500 broilers, divided into four treatments, with five replicates, each with 25 experimental units for each replicate, T0 without the addition of chamomile infusion to the drinking water plus conventional feed, T1 10% chamomile infusion was added to the drinking water plus conventional feed, T2 20% chamomile infusion was added to the drinking water plus conventional feed, T3 30% chamomile infusion was added to the drinking water plus conventional feed. The statistical analysis was carried out with the InfoStat computer system and the 5% Tukey test. The results obtained were as follows: weight gain per treatment T0: 2774.32 grams; T1: 3009.72 grams; T2: 2895.64 grams; T3: 783.64 grams. In the variable feed consumption per treatment T0: 24296 grams; T1: 23554 grams; T2: 25700 grams; T3: 26250 grams. In the variable consumption of chamomile-infused water per treatment in ml T0: 0 ml; T1: 8336 ml; T2: 8269 ml; T3: 8272.33 ml. In the variable feed conversion per treatment: T0: 1.75 gr; T1: 1.68 gr; T2: 1.83 gr and T3: 1.86 gr. In the mortality variable, 5% was obtained: T0 2 birds, T1 0 birds, T2 1 bird, T3 2 birds. The benefit-cost ratios were as follows: T0: 30%, T1:36%, T2: 31% and T3 29%.